2019
DOI: 10.3390/brainsci9100257
|View full text |Cite
|
Sign up to set email alerts
|

Epidemiology and Incidence of Pediatric Concussions in General Aspects of Life

Abstract: Background: Concussions are one of the most common head injuries acquired within the pediatric population. While sport-related concussions are well documented, concussions within other aspects of a child’s life are not as well researched. The purpose of this study is to examine the incidence of a large pediatric concussion population in a broad range of daily activities. Methods: Patients’ gender and nature of injury were extracted from 1408 medical records of patients who were diagnosed with a concussion at S… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
19
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(22 citation statements)
references
References 22 publications
3
19
0
Order By: Relevance
“…This is consistent with research that shows concussions in the school setting are most likely to occur during organized sports activities, especially among those who are high school age. 34,35 Elementary school age students are at increased risk for concussion during playground activities. 20 Still, within the school setting, concussions may occur outside of sports or physical activity, such as when a student slips and bumps their head in the classroom or in the hallway.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This is consistent with research that shows concussions in the school setting are most likely to occur during organized sports activities, especially among those who are high school age. 34,35 Elementary school age students are at increased risk for concussion during playground activities. 20 Still, within the school setting, concussions may occur outside of sports or physical activity, such as when a student slips and bumps their head in the classroom or in the hallway.…”
Section: Discussionmentioning
confidence: 99%
“…20 Still, within the school setting, concussions may occur outside of sports or physical activity, such as when a student slips and bumps their head in the classroom or in the hallway. 34 Or, concussions may occur outside of school as a result of a fall at home or a motor vehicle crash. 36 It is unclear if concussion policies related to professional development and those that prioritize return to the classroom before returning to athletics also improve identification and prevention of repeat concussions from non-sports-or physical activity-related causes.…”
Section: Discussionmentioning
confidence: 99%
“…Concussion injuries present a public health challenge that impacts many different professional and amateur sports [1], military training and deployment [2,3], and large pediatric [4], elderly [5], and civilian [6] populations. A concussion can lead to disruptions that are widespread throughout the brain [1,7].…”
Section: Introduction 1challenges In Concussion Diagnosis and Managementmentioning
confidence: 99%
“…During childhood and adolescence, organized sports activities (e.g., football, soccer) contribute to the majority of concussions among school‐age children (age 6 years and older) 1,6 . A recent study also found that concussions commonly occur when children are at school 7 . Additionally, males, children aged 10‐14 and 15‐17 years old, and contact sports had higher rates of pediatric emergency department visits for sports‐ and recreation‐related activities, though for younger children playground activities did account for a large percentage as well 8 .…”
mentioning
confidence: 99%
“…A study of pediatric patients seen in a sports concussion clinic found that concussions sustained at school most commonly occurred when a student was participating in physical education (PE) class, in a classroom, at recess, or in the hallway 7 . However, the context and circumstances that lead to a concussion in the school setting, as well as the action taken in response to the injury, has not been described in the published literature.…”
mentioning
confidence: 99%